Analyzing green-blue infrastructures using geographical information systems and remote sensing: A case study of Isparta - Elif Ela Nur Yavuz; E. Seda Arslan (Turkish Journal of Forestry)
The environmental issues arising from urbanization have spurred the development of urban planning approaches that conserve nature and ecosystems. Nature-based planning supports the formation of sustainable cities by promoting permeable surfaces and increasing biodiversity-supporting practices within metropolitan areas. In this context, the environmentally friendly approach known as blue-green infrastructure (BGI) has been adopted as a suitable method for mitigating the effects of climate change, which is recognized globally as an environmental issue and enhances urban resilience. Green infrastructure (GI) encompasses various components such as parks, gardens, forests, woodlands, and other open spaces, while blue infrastructure (BI) is specifically designed for water management and sustainability. In terms of improving urban life quality and preserving ecosystems, analyzing existing urban BGI using satellite imagery within a Geographic Information System (GIS) framework could facilitate the development of strategies to reduce the impacts of climate change in cities. Accordingly, in this study, BGI within the central district boundaries of Isparta City has been analyzed based on criteria such as size, quality, and impact area using QGIS software and remote sensing technologies. The role/effectiveness of BGI in mitigating potential climate change effects has been evaluated within this context. Additionally, a socio-ecological assessment was conducted to analyze the relationship between population and infrastructure based on transportation options in neighborhoods with BGI.